Meta-Analysis the Effects of Education, Pregnancy Planning, Husband Support, and Distance to Health Facilities on the Utilization of Antenatal Care Service - Sitepu, Fransiska; Tamtomo, Didik; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Antenatal care (ANC) is comprehensive and quality antenatal care provided to pregnant women in the form of antenatal checks to prevent causes of morbidity and mortality in pregnant women and children. The decrease in the number of visits of pregnant women to health facilities has resulted in high maternal mortality due to complications of pregnancy and childbirth. This study aimed to analyze the effect of education, pregnancy planning, husband's support, and distance to health facilities on the utilization of ANC. Subjects and Method: This was a meta-analysis. Population was pregnant women. Intervention: higher education, planned pregnancies, strong husband support, and distance to close facilities. Comparison: low education, unplanned pregnancies, weak spousal support, and long distances to facilities. Outcome: utilization of ANC. The articles used were obtained from Google Scholar, BMC Pregnancy and Childbirth, PubMed, and Science Direct. The keywords used “Antenatal Care” AND “Utilization of ANC” AND “Husband Support and ANC”. The articles used were full text in English from 2009 to 2022. Articles were selected using the PRISMA diagram and analyzed using the Review Manager 5.3 application. Results: 14 cross-sectional studies showed that mothers with higher education (aOR=2.93; 95% CI=1.93 to 4.45; p=0.001); planned pregnancy (aOR= 1.99; 95% CI= 1.26 to 3.15; p=0.003); had husband support (aOR=2.89; 95% CI= 1.23 to 6.81; p=0.020); and closer distance to health facilities (aOR=3.07; 95% CI=1.43 to 6.55; p=0.003) had high and significant posibility to utilize ANC. Conclusion: Higher education, pregnancy planning, husband's support, and proximity to health facilities influence the utilization of antenatal care. Keywords: antenatal care, pregnant women, morbidity. Correspondence: Fransiska Sitepu. Master's Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java 57126, Indonesia. Email: fransiskasitepu16@gmail.com. Mobile: +6281367655293.